2006
DOI: 10.1302/0301-620x.88b9.17588
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgery for reconstruction of fractures of the acetabulum

Abstract: This is a retrospective case review of 237 patients with displaced fractures of the acetabulum presenting over a ten-year period, with a minimum follow-up of two years, who were studied to test the hypothesis that the time to surgery was predictive of radiological and functional outcome and varied with the pattern of fracture. Patients were divided into two groups based on the fracture pattern: elementary or associated. The time to surgery was analysed as both a continuous and a categorical variable. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 17 publications
7
73
2
2
Order By: Relevance
“…14,[62][63][64][65][66][67][68][69] The recorded outcome of these difficult fractures has significantly improved reflecting the increasing expertise and the advances of rehabilitation. 12,[18][19][20]27,43,46,70,71 Acetabular fractures with elements of displacement and/or comminution of the quadrilateral plate or medial wall remain challenging especially in the presence of osteoporosis. For that reason we performed the present comprehensive review to define the course of management of this element of an acetabular fracture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,[62][63][64][65][66][67][68][69] The recorded outcome of these difficult fractures has significantly improved reflecting the increasing expertise and the advances of rehabilitation. 12,[18][19][20]27,43,46,70,71 Acetabular fractures with elements of displacement and/or comminution of the quadrilateral plate or medial wall remain challenging especially in the presence of osteoporosis. For that reason we performed the present comprehensive review to define the course of management of this element of an acetabular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,22,29,46 This relates to several factors including the increased incidence of medial wall fractures, comminution, associated intra-articular chondral and osseous injuries, pre-existing osteoarthritis and gaining secure fixation in osteoporotic bone. 11,17,19,22 Other factors related to an unfavourable outcome include delay to surgery, 18,22,68 morbid obesity and medical co-morbidities. 22 The surgical approach to quadrilateral plate fractures is dependent on the fracture pattern, whether the quadrilateral plate remains attached to one of the columns or is a separate displaced or comminuted fragment, the column or wall which appears mostly displaced, the planned method of fixation, as well as the surgical expertise and preference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studies reported good to excellent functional outcomes in 71-88% patients after surgical treatment of acetabular fractures [12][13][14][15]. The important prognostic factors to influence clinical outcome include associated fracture type, damage to the femoral head, associated injuries, dislocation at the time of injury, inadequate fracture reduction, age, development of heterotopic ossification, and a delay in surgical treatment [16][17][18][19][20][21]. In addition, the surgeon's training and expertise is a crucial factor [22].…”
Section: Introductionmentioning
confidence: 99%